Revisiting Bacille Calmette‐Guérin revaccination strategies: timing of immunization, Mycobacterium tuberculosis and non‐tuberculous mycobacteria infections, strain potency and standardization of randomized controlled trials - Wenping Gong; Jingli Du; Ashok Aspatwar; Li Zhuang; Yanlin Zhao (Wiley, 2024)
Abstract The persistent threat of tuberculosis (TB) on a global scale hasprompted a reevaluation of preventive strategies, with a particular focus onthe Bacille Calmette‐Guérin (BCG) vaccine's role in revaccination. Theresurgence underscores an urgent need for enhanced measures, prompting acritical examination of BCG revaccination strategies. Drawing from the researchof Paulo Cesar Pereira dos Santos and a synthesis of randomized controlledtrials (RCTs), this review identifies key considerations for refining BCGrevaccination's efficacy against Mycobacterium tuberculosis (MTB) andTB. The main body of this review integrates four principal domains essentialfor optimizing BCG revaccination: the timing of revaccination, the assessmentof various BCG strains, the evaluation of the vaccine's effectiveness on MTBand non‐tuberculous mycobacteria (NTM) strains, and the enhancement of RCTmethodologies. Determining the optimal revaccination timing is paramount forbolstering immunity, especially in regions with high TB prevalence. Theanalysis of different BCG strains provides insights into strain‐specificimmunogenicity, informing vaccine deployment strategies. Additionally,understanding the vaccine's impact on a range of mycobacterial infections iscrucial for its broader application in various microbial contexts. The reviewemphasizes the refinement of RCT designs to ensure robust and consistentoutcomes, facilitating the reproducibility of results in diverse settings. Itproposes a strategy that not only suggests modifications to revaccinationpractices to increase global TB prevention effectiveness but also calls forcontinuous research to improve BCG revaccination methodologies. The paperadvocates for a standardized, evidence‐driven approach to global TB preventionthat takes into account regional epidemiological differences. In conclusion,this review significantly contributes to the discourse on TB prevention,advocating for evidence‐based, standardized approaches that could potentiallytransform the role of BCG revaccination in global TB prevention efforts. Thefindings support current initiatives aimed at developing policies based onsolid evidence, ensuring the scientific integrity and practical relevance ofBCG revaccination strategies.